2015
DOI: 10.18320/jimd/201502.02111
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of feto-placental ratio

Abstract: Abstract:The dimension of delivered placentae mirrors the cumulative conception to parturition. Placental weight is the gross summary of fetal growth under the influence of many extrinsic and intrinsic factors. Hence, the present study evaluated the influence of gestation, sex of the newborn, and parity on feto singleton newborn from a teaching hospital of North Karnataka, India. Data was collected from August 2012 to January 2013 by using standard operating procedures deviations of placental morphometry, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Fetoplacental ratio and placental coefficient were similar between the two study groups in our study, whereas several studies have shown that these could be less for smallfor-gestational age and adverse pregnancy outcomes. 6,[16][17][18] In the present study, mean placental weight was significantly lower in low-birth-weight babies, which were similar to other studies. [19][20][21][22][23] Low mean placental weight in low-birth-weight babies in our study could be due to decompensatory changes in the placenta.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Fetoplacental ratio and placental coefficient were similar between the two study groups in our study, whereas several studies have shown that these could be less for smallfor-gestational age and adverse pregnancy outcomes. 6,[16][17][18] In the present study, mean placental weight was significantly lower in low-birth-weight babies, which were similar to other studies. [19][20][21][22][23] Low mean placental weight in low-birth-weight babies in our study could be due to decompensatory changes in the placenta.…”
Section: Discussionsupporting
confidence: 90%
“…Where ds -smallest diameter (placental breadth) and dl -largest diameter (placental length) -Feto placenta ratio was calculated using the formula: 6 Weight of fetus Weight of placenta -Placental coefficient was calculated using the formula: 6 Weight of placenta Weight of fetus…”
Section: × × Ds DLmentioning
confidence: 99%